A variable X‐ray chopper system for phase‐sensitive detection in synchrotron X‐ray scanning tunneling microscopy. (14th July 2020) - Rose, Volker; Ajayi, Tolulope; Rosenmann, Daniel; Shirato, Nozomi
Abstract : An ultra‐high‐vacuum compatible chopper system for operation at soft and hard X‐ray photon energies, a necessary component in synchrotron X‐ray scanning tunneling microscopy, has been developed. Abstract : An ultra‐high‐vacuum compatible X‐ray chopper system has been designed, constructed and integrated into the XTIP beamline at the Advanced Photon Source at Argonne National Laboratory. The XTIP beamline can operate at soft X‐ray energies from 400 eV to 1900 eV while providing a focused beam down to about 10 µm × 10 µm into the synchrotron X‐ray scanning tunneling microscopy (SX‐STM) endstation instrument. The X‐ray chopper is a critical component for separating topographic information from chemical information in SX‐STM through phase‐sensitive current detection. Depending on the experimental needs, the modulation frequency can be controlled from 100 Hz to 10 kHz. In addition, the chopper system is fully bakeable and can achieve a base pressure of 10 −10  mbar. Facilities for active water cooling have been designed, but passive cooling through copper braids has been shown to be sufficient at standard chopping frequencies. Using an Fe/Al2 O3 /CoAl(111) sample, the separation of the SX‐STM current into a chemical component and a stable feedback signal is demonstrated.